2018
DOI: 10.1101/416271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agricultural intensification reduces microbial network complexity and the abundance of keystone taxa in roots

Abstract: words) 1Root-associated microbes play a key role in plant performance and productivity, making 2 them important players in agroecosystems. So far, very few studies have assessed the impact 3 of different farming systems on the root microbiota and it is still unclear whether agricultural 4 intensification influences network complexity of microbial communities. We investigated the 5 impact of conventional, no-till and organic farming on wheat root fungal communities using 6PacBio SMRT sequencing on samples colle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 78 publications
11
94
1
Order By: Relevance
“…We found that all four fertilizer inputs induced speci c changes in the microbiome structure, a result that is similar to previous ndings tracking responses to different fertilization management regimes [71,72].…”
Section: Impact Of Biocontrol Agent On the Resident Soil Community Assupporting
confidence: 89%
“…We found that all four fertilizer inputs induced speci c changes in the microbiome structure, a result that is similar to previous ndings tracking responses to different fertilization management regimes [71,72].…”
Section: Impact Of Biocontrol Agent On the Resident Soil Community Assupporting
confidence: 89%
“…Since organic inputs provide a substantial supply of substrates and nutrients for soil microorganisms, previous studies indicated that organic inputs generally increased the complexity of soil microbial networks [33,35,36]. In contrast, we observed that residue retention simplified both soil bacterial and fungal co-occurrence networks in 2018.…”
Section: Bacterial and Fungal Co-occurrence Networkcontrasting
confidence: 54%
“…Similarly, the application of rice straw generated more substantial bacterial network connectivity in residue retained soils [35]. In a recent study, Banerjee et al [36] compared no tillage, conventional and organic agricultural systems and observed a significantly higher complexity of fungal networks in organic systems, whereas they did not find a difference between no-till and conventional tillage systems. However, information on the manner in which microbial co-occurrence networks respond to tillage and residue management is still limited.…”
mentioning
confidence: 98%
“…Twenty‐day‐old, in vitro ‐grown A. thaliana Col‐0 seedlings were transferred from liquid Hoagland medium (2.5 mM inorganic phosphate (Pi)) (Rodríguez‐Celma et al ., ) to 60 ml pots filled with soil from a field in the Reijerscamp nature reserve, the Netherlands (52°01′02.55″N, 5°77′99.83″E), where natural Arabidopsis populations grow as previously described (Berendsen et al ., ). Bulk soil pots were left unplanted.…”
Section: Methodsmentioning
confidence: 97%